Recombinant Human Cytochrome P450 1B1 Expression inEscherichia coli - Tsutomu Shimada; Rebecca M. Wunsch; Imad Hanna; Thomas R. Sutter; F.Peter Guengerich; Elizabeth M. J. Gillam (1998)
Human cytochrome P450 (P450) 1B1 was expressed inEscherichia coliat a level of 200 nmol/liter culture using a pCW vector by removal of codons 2–4 and modification of the nucleotide sequence of the resulting N-terminal seven codons; a similar level of expression was found with a bicistronic construct that also expressed human NADPH–P450 reductase. P450 1B1 was purified (from the monocistronic system) to electrophoretic homogeneity and a specific content of 9.2 nmol P450/mg protein using DEAE, CM, and hydroxylapatite chromatography. The absolute spectra showed a considerable fraction of high-spin iron and little cytochrome P420. The catalytic activity of the purified enzyme was considerably enhanced in the presence of cholate. Both reconstituted P450 1B1 and the bacterial membranes prepared from the bicistronic vector system had similar7-ethoxyresorufin O-deethylation activities; as expected, 17β-estradiol was hydroxylated primarily at the 4-position. The ability of human P450 1B1 to activate several heterocyclic amines and polycyclic hydrocarbon dihydrodiols was confirmed with reconstituted P450 1B1 and the P450 1B1 membranes in which NADPH–P450 reductase was coexpressed.